2016
DOI: 10.1097/md.0000000000001255
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of SELE A561C and G98T Variants With the Susceptibility to CAD

Abstract: Published genetic association studies have produced controversial results regarding the association of SELE gene polymorphisms (A516C and G98T) and CAD susceptibility. We therefore chose to perform a meta-analysis to determine the association.Twenty-seven eligible articles were identified through electronic databases, providing 5170 CAD cases and 4996 controls. Fixed-effects or random-effects summary ORs were calculated to estimate the risk of CAD in relation to A516C and G98T. Forest plots and funnel plots we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…SELE encodes E-selectin; variants in SELE have been associated with coronary artery disease and hypertension 6466 . BAG3 encodes for the Bcl2-associated athanogene 3 (BAG3) protein, a member of the BAG family of co-chaperones that interact with the heat shock protein 70 ATPase domain.…”
Section: Discussionmentioning
confidence: 99%
“…SELE encodes E-selectin; variants in SELE have been associated with coronary artery disease and hypertension 6466 . BAG3 encodes for the Bcl2-associated athanogene 3 (BAG3) protein, a member of the BAG family of co-chaperones that interact with the heat shock protein 70 ATPase domain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggested that the associations between two SNPs (AGTR1/rs2638360 and VSNL1/rs16983422) and SSBP were consistent among different salt loading manners. The SELE gene is expressed in cytokine-stimulated endothelial cells and appears to participate in the pathogenesis of atherosclerosis ( Liao et al, 2016 ). In the GenSalt study, SELE/rs5368 was significantly associated with decreased BP responses to low-sodium processes only in male.…”
Section: Discussionmentioning
confidence: 99%
“…So far, mainly two presumably functional SELE polymorphisms, A561C (rs5361) and G98T (rs1805193), have been investigated in different ethnic groups with respect to CAD [13, 14, 26]. However, the haplotype-based analysis may offer greater power in association studies than the analysis of one SNP at a time, especially when none of the investigated SNPs is a causative marker [27].…”
Section: Discussionmentioning
confidence: 99%